Psychological health and wellness and the impact of 6 weeks and 3 months supportive text messaging program (Wellness4MDs) among physicians and medical learners in Canada: a longitudinal study - Obeng Nkrumah, Samuel; Shalaby, Reham; Agyapong, Belinda; Eboreime, Ejemai; Kelderhouse, Charles; Agyapong, Vincent Israel Opoku (Frontiers in Public Health, 2025)
BackgroundPhysicians and medical learners face high rates of burnout, anxiety, and depression due to the demanding nature of their work. Many are reluctant to seek support because of stigma, time constraints, and limited access to care. Cognitive Behavioral Therapy (CBT)-based supportive SMS messaging offers a promising, scalable alternative.ObjectiveThis study evaluates the impact of Wellness4MDs, a CBT-based supportive messaging program, on the psychological health and well-being of physicians and medical learners in Canada.MethodsParticipants subscribed to the Wellness4MDs program and received daily supportive SMS messages for 3 months. Standardized self-rated web-based questionnaires assessing depression, anxiety, burnout symptoms were collected at baseline, 6 weeks, and 3 months using the PHQ-9, GAD-7, MBI, and WHO-5. Subscribers’ satisfaction was measured using an online, self-developed questionnaire adapted from tools previously employed to assess similar programs.ResultsA total of 806 subscribers participated, with 226 completing the baseline survey. 66 participants completed surveys at all follow-up points, and 53 completed both baseline and at least one follow-up survey. At the three-month follow-up, there were statistically significant reductions in mean scores for emotional exhaustion (EE) and anxiety symptoms (GAD-7), with reduction from baseline of 16.1% (t = 2.86, p = 0.01) and 15.5% (t = 2.05, p = 0.05) with effect sizes of 0.4 and 0.3 respectively, indicating moderate effects. These reductions remained statistically significant when missing data were imputed using the last observation carried forward (LOCF) method. However, no significant changes were observed on the PHQ-9 scale. The overall mean satisfaction score for the Wellness4MDs program was 7.98 (SD = 2.06). Most participants reported that the messages helped them cope with stress (72.7%), anxiety (70.5%), depression (51.1%), and loneliness (42.0%). Additionally, 71.6% felt more connected to a support system, and 78.4% reported improved overall mental well-being.ConclusionWellness4MDs demonstrated effectiveness in reducing emotional exhaustion and anxiety symptoms. Its high user satisfaction, accessibility, and low-cost delivery model make it a promising complement to traditional mental health services for healthcare professionals.